Associação e densidade populacional de ácaros predadores em plantas de erva-mate Ilex paraguariensis St. Hil. (Aqüifoliaceae) na presença ou na ausência de ácaros fitófagos Association and populational density of mites predators in the mate-tea tree Ilex paraguariensis St. Hil. (Aqüifoliaceae) with or without the presence of phytophagous mites - Alfredo de Gouvea; Carla Felicita Zanella; Sergio Miguel Mazaro; Joel Donazzolo; Luis Francisco Angeli Alves (Ciência Rural, 2007)
O objetivo deste trabalho foi avaliar a associação e a concentração de ácaros predadores em plantas de erva-mate Ilex paraguariensis St. Hil. (Aqüifoliaceae) na presença ou não de ácaros fitófagos. O trabalho foi realizado em plantação comercial em Dois Vizinhos, PR, de agosto de 2001 a julho de 2002. Procederam-se coletas mensais de folhas de diferentes partes da planta. A contagem dos ácaros nas folhas foi realizada em laboratório com auxílio de microscópio estereoscópico. Foram constadas duas espécies de ácaros fitófagos, Dichopelmus notus Keifer e Oligonychus yothersi (McGregor), e três espécies de predadores, Euseius concordis (Chant), Iphiseiodes zuluagai Denmark & Muma e Agistemus sp., associadas às plantas de erva-mate. Foi observada associação de E. concordis e I. zuluagai a folhas com presença de D. notus e de Agistemus sp. a plantas com presença de D. notus e maior densidade populacional de E. concordis e de I. zuluagai em plantas com D. notus. This research was aimed at evaluating the association and concentration of predators mites in the mate-tea tree Ilex paraguariensis St. Hil. (Aqüifoliaceae) with or without phytophagous mites. This study was conduced at Dois Vizinhos, State of Paraná, from August 2001 to July 2002, in a mate-tea tree commercial plantation. Leaf samples from different parts of the plant were taken monthly, and the number of mites was counted in laboratory. Two species of phytophagous mites, Dichopelmus notus Keifer and Oligonychus yothersi (McGregor), and three species of predator mites Euseius concordis (Chant), Iphiseiodes zuluagai Denmark & Muma, and Agistemus sp. were related to the mate-tea plant. The association of E. concordis and I. zuluagai to the leaves with D. notus, the association of Agistemus sp. to the plants with D. notus and a higher population density of E. concordis and I. zuluagai in plant with D. notus were observed.